2015
DOI: 10.1016/j.joa.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of esophageal temperature monitoring guided atrial fibrillation ablation on preventing asymptomatic excessive transmural injury

Abstract: BackgroundEven with the use of a reduced energy setting (20–25 W), excessive transmural injury (ETI) following catheter ablation of atrial fibrillation (AF) is reported to develop in 10% of patients. However, the incidence of ETI depends on the pulmonary vein isolation (PVI) method and its esophageal temperature monitor setting. Data comparing the incidence of ETI following AF ablation with and without esophageal temperature monitoring (ETM) are still lacking.MethodsThis study was comprised of 160 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…acute pyloric spasms and gastric hypomotility). The incidence of oesophageal injury after radiofrequency (RF) ablation of AF has been reported to range from 2.9% to 50% (mostly as localised erythema), depending on the RF power settings and ablation strategies [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…acute pyloric spasms and gastric hypomotility). The incidence of oesophageal injury after radiofrequency (RF) ablation of AF has been reported to range from 2.9% to 50% (mostly as localised erythema), depending on the RF power settings and ablation strategies [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid these complications, real-time intraluminal oesophageal temperature monitoring during ablation with the oesophageal temperature probes advanced to the level of the LA could be used. Additionally, the probe could be a marker of the oesophageal lumen location in relation to PV ostia [3,12,[14][15][16][17]. It was reported that the use of temperature monitoring significantly reduces the oesophageal injury ratio (6% vs. 36%, p < 0.006) without any serious complications related to the probe [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to reduce esophageal injury have included the use of esophageal temperature probes to monitor esophageal heating during AF ablation. Prior work has shown a reduction in esophageal injury in cases supported by esophageal temperature monitoring though recent literature has been less conclusive . Small series have shown variability in esophageal heating during AF ablation dependent on esophageal location .…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown a reduction in esophageal injury in cases supported by esophageal temperature monitoring though recent literature has been less conclusive. 10,11 Small series have shown variability in esophageal heating during AF ablation dependent on esophageal location. 12 Compared to patients without confinement, we found those with esophageal confinement had significantly higher peak ELT during AF ablation relative to baseline ELT derived from recordings throughout the duration of ablation.…”
Section: Acute Complicationsmentioning
confidence: 99%
“…8,11) On the other hand, Kiuchi, et al demonstrated a benefit for using an ETP with decreased esophageal injury. 16) Keshishian, et al reported a series of three patients with mucosal erythema and shallow and deep ulceration after PVI. 17) The EDEL documented in our study resemble those lesions reported by other groups with all EDEL healed in between two weeks.…”
Section: Discussionmentioning
confidence: 99%